THE INFLUENCE OF CUSTOMER VALUE AND SERVICECAPE ON CUSTOMER LOYALTY CASE STUDY OF HIZZY COFFEE MEDAN - Ardiansyah, Romi; Sembiring, Beby Karina Fawzeea; Aritonang, Evawany Yunita (Program Pascasarjana UIN Sumatera Utara, 2025)
This study aims to analyze the influence of Customer Value and Layout on Customer Loyalty at Hizzy Coffee Medan as one of the representations of local coffee shop businesses. The research method used combines a quantitative approach through descriptive analysis and multiple linear regression analysis to test the relationship between the variables studied. Data were obtained from distributing questionnaires to active Hizzy Coffee customers. The results of the study indicate that both customer value and layout simultaneously have a positive and significant effect on customer loyalty. Specifically, layout has a dominant contribution in influencing customer loyalty, where comfortable, aesthetic, and functional room arrangements encourage increased customer satisfaction and repeat visits. These findings emphasize the importance of coffee shop management in maintaining and developing service quality, physical facilities, and interior design that are in accordance with customer preferences. The practical implications of this study provide recommendations for Hizzy Coffee managers and the coffee shop industry in general to integrate strategies for strengthening customer value and optimizing layout as an effort to build sustainable customer loyalty.